2*6*(-1+3) = 24
(2 + 6) * 1 * 3 = 24.
To make 24 using 1, 3, 4, and 6, you can use the following mathematical operations: (6 / (1 - (3/4))). This equation breaks down as follows: first, divide 6 by (1 - (3/4)), which simplifies to 6 / (1 - 0.75) = 6 / 0.25 = 24. Therefore, using these numbers and operations, you can make 24.
3*(6-5)*8 = 3*1*8 = 24
8*(8 + 1 - 6) = 8*3 = 24
Assuming you have to use ALL the numbers.... 6 - 5 = 1 then 3 x 8 = 24. 24 x 1 = 24.
6 x [3 + (5-4)] = 6 x (3 + 1) = 6 x 4 = 24
(2+1+1) x 6 = 24 (9-1) x 3 = 24 ((9+1) x 2)+1+3 = 24
One possible solution: (3 + 3)*(1*3/3 + 3) = 6 * 4 = 24
To make 24 with the numbers 3, 3, 6, and 8, you can use the following equation: (8 / (3 - (6 / 3))). Here's the breakdown: first, divide 6 by 3 to get 2. Then, subtract 2 from 3 to get 1. Finally, divide 8 by 1 to get 8. When you multiply 8 by the result of the subtraction, which is 8, you get 24.
Six and they are: 1*1*24 1*2*12 1*3*8 1*4*6 2*2*6 2*3*4
8 x (8 + 1 - 6) = 8 x 3 = 24